Disease management teams in oncology: State of the art and the experience of a scientific institute of hospitalization and treatment (IRCCS) in Rome, Italy - Marialuisa Appetecchia; Carlotta Amantea; Marco Canfora; Fabrizio Petrone; Gennaro Ciliberto; Ermete Gallo; Laura Figorilli (Brain, Behavior, & Immunity - Health)
Background: This article analyzes the main coordination needs linked to the diagnosis and treatment of oncological diseases, presenting the various integration tools that our healthcare organization adopted to guarantee continuity of care at the IRCCS IFO (Istituto di Ricovero e Cura a Carattere Scientifico Istituti Fisioterapici Ospitalieri) in Rome. The object of investigation is the disease management team (DMT) organization for the diagnosis and treatment of people suffering from oncological disease and the consequences in terms of improving their management. Methods: The study focuses, in particular, on the analysis of the different organizational methods chosen for the management of activities related to diagnosis and treatment paths. Results: The results, although preliminary, highlight a great variability in the adoption of integrated organizational models by the different DMTs compatible with the heterogeneity of oncological diseases. Conclusion: The results of this study have highlighted that, despite the diversity of the different DMTs created for different oncological pathologies, DMTs guarantee a patient-centered approach and the creation of shared databases, which facilitates the evaluation of progress and the identification of areas for improvement. This analysis has allowed us to obtain a useful map of the models used by the different DMTs, also laying the foundations for more precise evaluations of their effectiveness. The correct evaluation of the effectiveness of DMTs acquires great importance today, especially if we consider that empirical evidence is not yet in agreement on the real effectiveness of this tool with respect to both the qualitative dimension and the efficiency of interventions.